2012
DOI: 10.4267/2042/48134
|View full text |Cite
|
Sign up to set email alerts
|

La question de la vulnérabilité et de l'adaptation de l'agriculture sahélienne au climat au sein du programme AMMA

Abstract: RésuméÀ ces fluctuations climatiques récentes s'ajoutent les conséquences attendues du changement climatique. Le quatrième rapport (AR4) du Groupe d'experts intergouvernemental sur l'évolu-tion du climat (GIEC), publié en 2007, a en effet alerté la communauté internationale sur l' augmentation de la température partout dans le monde ainsi que sur la probable augmentation de la fréquence et de l'intensité des aléas météorologiques majeurs comme les sécheresses, en citant l'Afrique comme le continent le plus vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…These include: (i) agronomic modeling which is a tool for quantifying the link between climate and agriculture. it is a model that can be used to transcribe climate information for example temperature and/or precipitation in terms of agronomic variables such as agricultural yields, biomass in order to synthesize existing knowledge about climate and plant relationships (Sultan, 2012); (ii) empirical modeling consists in constructing a link between dependent variables (eg performance) and explanatory variables without explicitly representing the agronomic mechanisms (Sultan, 2012(Sultan, , 2011. It is a method for modeling the effects of meteorology and climate on crops and consists in making direct statistical comparisons between meteorological and climatic elements and actual yields (Roberts and al., 2012); (iii) the Ricardian approach developed by Mendelsohn and al.…”
Section: 1 Econometric Modelmentioning
confidence: 99%
“…These include: (i) agronomic modeling which is a tool for quantifying the link between climate and agriculture. it is a model that can be used to transcribe climate information for example temperature and/or precipitation in terms of agronomic variables such as agricultural yields, biomass in order to synthesize existing knowledge about climate and plant relationships (Sultan, 2012); (ii) empirical modeling consists in constructing a link between dependent variables (eg performance) and explanatory variables without explicitly representing the agronomic mechanisms (Sultan, 2012(Sultan, , 2011. It is a method for modeling the effects of meteorology and climate on crops and consists in making direct statistical comparisons between meteorological and climatic elements and actual yields (Roberts and al., 2012); (iii) the Ricardian approach developed by Mendelsohn and al.…”
Section: 1 Econometric Modelmentioning
confidence: 99%
“…Also, the agricultural system that prevails in most African countries remains rain-fed, therefore highly depend on climatic conditions [10]. It explains the relatively high sensitivity of the agricultural sector to climate change [11].…”
Section: Introductionmentioning
confidence: 99%
“…For this part of the population, agriculture is the main source of livelihood [7]. In West Africa in particular, the agricultural sector plays a decisive role in terms of national economies, employment, income of rural households, the balance of the trade balance and the food security of the population [8]. This agriculture contributes about 35% of gross domestic product (GDP) in West Africa [7].…”
Section: Introductionmentioning
confidence: 99%
“…This agriculture contributes about 35% of gross domestic product (GDP) in West Africa [7]. In the current context of climate change, without appropriate adaptation measures, this agriculture, already threatened by rapid population growth and reduced access to technological change [8] is likely to increase in fragility. [9], in their work, also concluded that in the face of the pronounced climatic variations experienced by West Africa since the 1970s, adaptation methods are appeared to be the only alternatives for reducing the vulnerability of rural populations [9].…”
Section: Introductionmentioning
confidence: 99%